SPECIFIC POLYMERS - Functional Polymers and Materials for Optoelectronic Devices and Sensors. (2016) - Graillot, A.; Bouvet-Marchand, A.; Loubat, C.
Abstract: SPECIFIC POLYMERS is a SME acting as R&D service provider in the field of functional monomers, polymers and materials with high specificity. In more than 12 years, SP has developed the synthesis of more than 1000 functional building blocks, monomers and polymers and is now working with more than 400 customers and partners in more than 30 countries worldwide in all field of applications such as surface finishing (glass, metal, metal oxides, nanoparticles, plastics), aeronautic, automotive, pharmaceutical industry, cosmetic, electronic, optic, energy (fuel cells, solar cells or lithium batteries). Since 2013, SP is developing innovative materials for electronic devices. As for example, SP is involved in PiezoMAT European Project and develops UV-crosslinkable thin layer polymeric materials for the encapsulation of ZnO nanowires (NWs) in multi-NWs pressure based fingerprint sensors.